Subclassification of small bowel Crohn's disease using magnetic resonance enterography: a review using evidence-based medicine methodology. Issue 12 (December 2015) - Murphy, D.J.; Smyth, A.E.; McEvoy, S.H.; Gibson, D.J.; Doherty, G.A.; Malone, D.E.
Abstract : Magnetic resonance enterography (MRE) has a growing role in imaging small bowel Crohn's disease (SBCD), both in diagnosis and assessment of treatment response. Certain SBCD phenotypes respond well to biologic therapy and others require surgery; MRE has an expanding role in triaging these patients. In this review, we evaluate the MRE signs that subclassify SBCD using evidence-based medicine (EBM) methodology and provide a structured approach to MRE interpretation.